2013
DOI: 10.1002/jcla.21605
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Fetuin‐A, Cystatin‐C Levels, and Microalbuminuria in Patients With Metabolic Syndrome

Abstract: In our study, we found that MS patients with microalbuminuria had high levels of fetuin-A and cystatin-C. In conclusion, we suggest that determination of fetuin-A and cystatin C levels could be useful marker as an early indicator of renal injury in patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
6
1
1
Order By: Relevance
“…In addition, a decline in the renal function of patients with diabetes was not always accompanied by an increased microalbuminuria . While considerable studies have been verified that the serum levels of cystatin C was positively correlated with microalbuminuria and eGFR in diabetic or metabolic syndrome patients . Our study results further confirmed that cystain C could be quite an ideal indicator that represents renal function in diabetic patients instead of serum creatinine.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, a decline in the renal function of patients with diabetes was not always accompanied by an increased microalbuminuria . While considerable studies have been verified that the serum levels of cystatin C was positively correlated with microalbuminuria and eGFR in diabetic or metabolic syndrome patients . Our study results further confirmed that cystain C could be quite an ideal indicator that represents renal function in diabetic patients instead of serum creatinine.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to some previous reports in non-T1D cohorts, fetuin A levels were not associated with dyslipidemia, any single lipid parameter [8, 9, 14, 55], or microalbuminuria [57]. The missing association with blood pressure has also been reported in nondiabetic adults [54].…”
Section: Discussioncontrasting
confidence: 51%
“…Bu çalışmalarda, nefroloji bilim dalında sık takip edilen böbrek hastalıkları ile yapılan on adet bilimsel yayının olması dikkat çekmekteydi (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified